O5 Worldwide trends in all-cause mortality of auto-immune systemic diseases between 2001 and 2014. (23rd March 2020) - Scherlinger, Marc; Mertz, Philippe; Sagez, Flora; Meyer, Alain; Felten, Renaud; Chatelus, Emmanuel; Javier, Rose-Marie; Sordet, Christelle; Martin, Thierry; Korganow, Anne-Sophie; Guffroy, Aurélien; Poindron, Vincent; et al.
Abstract : Background: Although diagnosis, treatment and prevention strategies of Systemic Lupus Erythematosus (SLE) have further improved during the last two decades, the net benefit in term of global SLE-related mortality remains unknown. Objectives: To describe the worldwide trends in SLE mortality between 2001 and 2014 using data of 84 available countries from the World Health Organization (WHO) mortality database. To modelize SLE-related deaths taking into account temporal changes, geographical localization and country wealth. Methods: We analyzed the WHO mortality database containing cause-specific mortality of participating countries. SLE-related deaths were identified using the international classification of disease 10 (ICD-10, code M32*). In all countries which provided data between 2001 and 2014, age-standardized mortality rate (ASMR) was calculated for each year using the WHO reference population database. To have a better understanding of mortality fluctuations, countries were grouped geographically by continents and their nominal gross domestic product (GDP) per capita were retrieved from the United Nation database. The association between gender, geographical areas and disease-specific mortality was analyzed using multivariate Poisson regression. Results: Between 2001 and 2014, a total of 83, 639 SLE-related deaths occurred in 84 countries, which accounted for 0.02% of all deaths during the same period. Globally, the ASMR slightly increased between 2003 and 2014 (+0.58%/year, p<0.01), principally driven by an increase in Asia and Latin America (2.87%/yr and +2.20%/yr, respectively; p<0.0001). During the 2001–2014 period, the ASMR significantly decreased in Europe, North America and Oceania (-1.43%/yr, -3.49 and -2.93%, respectively; p<0.01 for all). In 2014, the SLE ASMR of Europe (1.06 [95%CI: 0.98–1.13] deaths/millions) was significantly lower than that of Latin America (5.53 [5.33 – 5.73], p<0.0001), North America (2.69 [2.53 – 2.84], p<0.0001), Asia (2.16 [2.03–2.29], p<0.0001) and Oceania (1.33 [0.97 – 1.70], p<0.01). Finally, we found a negative correlation between country wealth (GDP) and the SLE ASMR (r =-0.394, p<0.001). Conclusion: We observed drastic differences in the evolution of SLE-related mortality due to country geographic localization and country wealth.